The Verbal Interaction Social Threat Task: A New Paradigm Investigating the Effects of Social Rejection in Men and Women - Tops, Sanne; Habel, Ute; Abel, Ted; Derntl, Birgit; Radke, Sina (Frontiers in Neuroscience, 2019)
Social interactions are no longer bound to real-life encounters, but more often happen from behind a screen. Mimicking an online communication platform, we developed a new, fMRI compatible, social threat paradigm to investigate sex differences in reactions to social rejection. During the Verbal Interaction Social Threat Task (VISTTA) participants initiate 30 short conversations by selecting one of four predefined opening sentences. Two computerized interlocutors respond to the opening sentence mostly with negative comments and rejections towards the participant, which should induce social-evaluative threat. Physiological and subjective responses were measured, before, during and after the VISTTA in 61 (29 male, 32 female) first year students who received mostly negative (n=31; threat group) or neutral comments (n=30; control group). Two-level behavioral validation included social threat-induced mood changes in participants, and interlocutor evaluation. The latter consisted of multiple variables such as ‘willingness to cooperate’ after every conversation, an overall fairness evaluation of interlocutors, and evaluations per reaction indicating how positive or negative it was received. We acquired additional physiological measures including cortisol assays via saliva samples, heart rate and blood pressure. Confirming our hypotheses, peer rejection and exclusion during the VISTTA led to less willingness to cooperate and lower fairness evaluation of interlocutors. It also induced feelings of anger and surprise and lower happiness in the social-threat group. Women showed overall higher emotion ratings compared to men. Contrary to our hypothesis, the VISTTA did not induce cortisol and heart rate increases. However, the stable cortisol response in women in the threat group does not follow the circadian decline and might reflect an endocrinological response. The decline in cortisol response in men in both the threat and control group could indicate faster habituation to the VISTTA. Together, these findings indicate social-evaluative threat on a behavioral level, and moderate effects on the emotional and physiological level. Sex differences in affective and cortisol responses may indicate that women are more susceptible for social-evaluative threat than men. With a realistic implementation of verbal, interactive and social components, the VISTTA is designed as an fMRI paradigm that can be applied to elucidate the neural representation of social-evaluative threat.